2008
DOI: 10.1186/1745-6673-3-9
|View full text |Cite
|
Sign up to set email alerts
|

Effort-reward imbalance and overcommitment in employees in a Norwegian municipality: a cross sectional study

Abstract: Background: The aim of this study was to validate a Norwegian version of the Effort-Reward Imbalance Questionnaire (ERI-Q).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 32 publications
6
62
2
4
Order By: Relevance
“…Among them, two studies examined back and neck pain separately and showed that the association with effort-reward imbalance was stronger for neck pain than for back pain 17,21) . Other studies showed an association of effort-reward imbalance with shoulder pain 8) , upper extremity pain 9) , neck/upper-extremity injury 17) , low back and neck injury 21) and musculoskeletal symptoms (nonspecified) 19,23) . Our results among men are in agreement with these studies, except for upper extremity symptoms that did not display any association with effortreward imbalance in our study.…”
Section: Comparison With Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Among them, two studies examined back and neck pain separately and showed that the association with effort-reward imbalance was stronger for neck pain than for back pain 17,21) . Other studies showed an association of effort-reward imbalance with shoulder pain 8) , upper extremity pain 9) , neck/upper-extremity injury 17) , low back and neck injury 21) and musculoskeletal symptoms (nonspecified) 19,23) . Our results among men are in agreement with these studies, except for upper extremity symptoms that did not display any association with effortreward imbalance in our study.…”
Section: Comparison With Literaturementioning
confidence: 99%
“…Studies exploring the association between this conceptual model and musculoskeletal disorders are still lacking. Some studies have suggested that effort-reward imbalance and/or overcommitment may be associated with musculoskeletal pain in various working groups, including hotel room cleaners 8) , hospital workers 17) , nurses 18) , call center computer operators 9) , transport employees [19][20][21] , dental technicians 22) and public sector employees 23) . The objectives of this study were to explore the associations between biomechanical and psychosocial work factors and musculoskeletal symptoms in a sample of vineyard workers using a validated instrument for measuring effort-reward imbalance model and biomechanical factors relevant to this population.…”
Section: Abstract: Biomechanical and Psychosocial Work Exposures And mentioning
confidence: 99%
See 1 more Smart Citation
“…En terminant, notons que certaines études empiriques confirment la contribution de ce modèle vis-à-vis de la détresse psychologique (Calnan et al, 2004;Dragano et al, 2008;Lau, 2008;Li et al, 2006 (Stansfeld et al, 1999;Van Vegchel et al, 2001). Par ailleurs, le fait que ce modèle soit relativement récent explique le peu d'étude ayant été en mesure de le supporter.…”
Section: ( Overcommitment)unclassified
“…This tracking instrument, designed by the National Institute of Mental Health (NIMH) of the United States, aim to identify depressive mood in population studies. It measures the presence of current depressive symptoms, with an emphasis on the affective component and depressive mood 17 . The CES-D scale was validated in different populations 21,22 and used in several countries such as Germany 8 , Japan 9 , Holland 23 , Luxemburg 24 and Brazil…”
Section: Ces-d Scalementioning
confidence: 99%